2019
DOI: 10.1111/jeb.13533
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of inbreeding depression in fast declining herds of migratory caribou

Abstract: Identifying inbreeding depression early in small and declining populations is essential for management and conservation decisions. Correlations between heterozygosity and fitness (HFCs) provide a way to identify inbreeding depression without prior knowledge of kinship among individuals. In Northern Quebec and Labrador, the size of two herds of migratory caribou (Rivière‐George, RG and Rivière‐aux‐Feuilles, RAF) has declined by one to two orders of magnitude in the last three decades. This raises the question o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 90 publications
0
18
1
Order By: Relevance
“…As a result, a correlation between allelic diversity indices and performance would give support to the general effect hypothesis if other indices did not correlate with performance. We did not expect to observe such pattern, as we had previously shown that the caribou populations studied here do not suffer from inbreeding depression (Gagnon et al 2019). Instead, we predicted that direct effects were more likely to be involved in a potential correlation between MHC diversity and performance.…”
Section: Introductionmentioning
confidence: 62%
“…As a result, a correlation between allelic diversity indices and performance would give support to the general effect hypothesis if other indices did not correlate with performance. We did not expect to observe such pattern, as we had previously shown that the caribou populations studied here do not suffer from inbreeding depression (Gagnon et al 2019). Instead, we predicted that direct effects were more likely to be involved in a potential correlation between MHC diversity and performance.…”
Section: Introductionmentioning
confidence: 62%
“…In a recent study of two eastern migratory caribou populations, correlations between heterozygosity and fitness (HFCs) found no evidence of inbreeding depression (Gagnon et al, 2019). Notably, eastern migratory caribou from one of these population were also included in our study and had relatively low inbreeding estimates (FROH = 0.05-0.07).…”
Section: Islands Of Heterozygositymentioning
confidence: 86%
“…We selected two barren-ground caribou samples from the Qamanirijuaq population that ranges over northern Manitoba and Nunavut, a large population that was estimated to contain 264,661 individuals in 2014 and has not experienced dramatic historical or recent declines (COSEWIC, 2016). Within the eastern migratory ecotype, we included two samples from the George River population, Quebec, which has experienced a dramatic population decline over recent decades from approximately 823,000 individuals in 1993 (Couturier, Courtois, Crépeau, Rivest, & Luttich, 1996), to approximately 8,900 individuals in 2016 (Gagnon et al, 2019); our samples were obtained in 2008, after population declines had already occurred. We also included two eastern migratory caribou from the Pen Island population in northern Ontario, which was estimated to contain 16,638 individuals in 2011 (COSEWIC, 2017a).…”
Section: Caribou Samplingmentioning
confidence: 99%
See 2 more Smart Citations